Inovasi Video Pembelajaran Matematika Berbasis YouTube: Solusi Interaktif untuk Materi Konsep Aljabar Siswa Kelas VII - Rizaldi Khairun Nuzul; Anita Khumairoh; Faridah Hamidah Iswahyudi; Diva Putri Vania; Tri Fajar Yuliarti; Eka Septiani (Asosiasi Riset Ilmu Matematika dan Sains Indonesia, 2025)
Mathematics is often perceived as a subject that is difficult for students to master, a notion that has been confirmed by numerous previous studies. One of the contributing factors is the limited variety of instructional media used in classrooms, which affects students' interest and comprehension. Many teachers still lack appropriate learning media to support blended learning approaches. This study aims to develop and implement multimedia-based Educational Instructional Media (EIM) that are valid, practical, and effective. The project utilizes video-based learning to deliver algebra concepts material for Grade VII students at SMPN 252 Jakarta and SMPIT Al-Qudwah. The development process follows the ADDIE model, which includes five stages: analysis, design, development, implementation, and evaluation. During the analysis phase, both learning needs and content requirements were mapped according to SAP (System Analysis and Product). The material was then divided into seven core sections. In the design stage, the curriculum structure, system flow, and user interface were developed. The development stage involved creating instructional content based on the analysis results. The content was then uploaded to the Moodle platform and presented using the Project-Based Learning (PjBL) model.